1979
DOI: 10.1104/pp.64.5.780
|View full text |Cite
|
Sign up to set email alerts
|

Germination-induced Changes in Chromosomal Proteins of Spring and Winter Wheat Embryos

Abstract: The template activity of chromatin from winter wheat embryos gradually increased during germination and was regulated with some nonhistone proteins different from the two major ones, molecular weight 39k and 59k polypeptides, previously reported.To clarify chromosomal proteins which are involved in regulation of template activity of chromatin, we studied the quantitative and qualitative changes in chromosomal proteins. Differences In wheat embryos the activities to synthesize mRNA, rRNA, and tRNA were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Nicklisch et al (1976) reported changes in HI variants in different regions of corn root tips, and Faulde and NagI (1987) have reported cultivar, organ and herbicide treatment-specific variation of histone HI in maize. Sugita et al (1979) presented data indicating that the HI variant. Hid, is slightly reduced 48 h after germination of wheat embryos.…”
Section: Histone Variants In Plantsmentioning
confidence: 99%
“…Nicklisch et al (1976) reported changes in HI variants in different regions of corn root tips, and Faulde and NagI (1987) have reported cultivar, organ and herbicide treatment-specific variation of histone HI in maize. Sugita et al (1979) presented data indicating that the HI variant. Hid, is slightly reduced 48 h after germination of wheat embryos.…”
Section: Histone Variants In Plantsmentioning
confidence: 99%
“…As has been found in animal systems, the relative amount of an HI subtype can vary during plant development. For example, Sugita et al (1979) reported a decrease in the relative amount of variant Hld upon germination of wheat embryos.…”
mentioning
confidence: 99%
“…For example, mammals typically have at least seven electrophoretically distinct HI histone subtypes; each of which is encoded by a separate gene. For example, Sugita et al (1979) reported a decrease in the relative amount of variant Hld upon germination of wheat embryos. As has been found in animal systems, the relative amount of an HI subtype can vary during plant development.…”
mentioning
confidence: 99%